A LEGAL REVIEW OF THE HANDLING OF MONEY LAUNDERING CRIMINAL ACTS ORIGINATING FROM BITCOIN-BASED INVESTMENT CRIMES - Iqbal Nusantara Al Goni (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study examines the phenomenon of law enforcement against money laundering originating from investment fraud using cryptocurrency (particularly Bitcoin) in Indonesia. In the digital era, the development of information technology has created new investment opportunities through crypto assets, but on the other hand, it has given rise to new financial crime risks such as cyber laundering. The use of virtual currencies has become a preferred method for criminals due to the anonymous and cross-border nature of transactions, making it difficult for authorities to track them. This study uses a descriptive qualitative approach with a library research type. Data sources used include primary legal materials such as Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering, as well as secondary legal materials in the form of relevant literature and scientific journals. The results of the study indicate that the law enforcement mechanism against perpetrators of crypto-based money laundering in Indonesia faces significant challenges, both from regulatory aspects that do not specifically regulate the confiscation of digital assets and limited infrastructure and understanding of law enforcement officers regarding blockchain technology. The legal analysis focuses on classifying the perpetrators' actions in the money laundering stages: placement, layering, and integration. It also focuses on how policy formulation, application, and legal execution can be optimized to address evolving modus operandi along with technological advances.